A chloroplast-derived Toxoplasma gondii GRA4 antigen used as an oral vaccine protects against toxoplasmosis in mice - Yacono, Maria del Lujan (2012)
The parasitic protozoan Toxoplasma gondii, the causal agent of toxoplasmosis, can infect most mammals and birds. In human medicine, T. gondii can cause complications in pregnant women and immunodeficient individuals, while in veterinary medicine, T. gondii infection has economic importance due to abortion and neonatal loss in livestock. Thus, the development of an effective anti-Toxoplasma vaccine would be of great value. In this study, we analysed the expression of T. gondii GRA4 antigen by chloroplast transformation (chlGRA4) in tobacco plants and evaluated the humoral and cellular responses and the grade of protection after oral administration of chlGRA4 in a murine model. The Western blot analysis revealed a specific 34-kDa band mainly present in the insoluble fractions. The chlGRA4 accumulation levels were approximately 6 μg/g of fresh weight (equivalent to 0.2% of total protein). Oral immunization with chlGRA4 resulted in a decrease of 59% in the brain cyst load of mice compared to control mice. ChlGRA4 immunization elicited both a mucosal immune response characterized by the production of specific IgA, and IFN-γ, IL-4 and IL-10 secretion by mesenteric lymph node cells, and a systemic response in terms of GRA4-specific serum antibodies and secretion of IFN-γ, IL-4 and IL-10 by splenocytes. Our results indicate that oral administration of chlGRA4 promotes the elicitation of both mucosal and systemic balanced Th1/Th2 responses that control Toxoplasma infection, reducing parasite loads.